The Influence of Organizational Culture, Workload, And Work Motivation on Employee Job Satisfaction (Case Study at PT. Multitech Yasa Guna) - Bryan Denovan Pane; Nia Kusuma Wardhani (CV Edukastra Mandiri, 2025)
This research aims to analyze the effectiveness of implementing the Official Assessment System-based regional tax collection on Urban and Rural Land and Building Tax (PBB-P2) in Bekasi City. The research method used is empirical juridical with a descriptive approach through field studies, direct interviews with officials of the Bekasi City Regional Revenue Agency (Bapenda), and documentation of PBB-P2 revenue realization data in 12 sub-districts and 56 villages. The results indicate that the implementation of PBB-P2 in Bekasi City is less effective, despite a clear legal basis according to Law Number 1 of 2022 and Bekasi City Regional Regulation Number 1 of 2024. The highest PBB-P2 revenue realization was in Medan Satria Sub-district at only 81.16%, while the lowest was in Jatiasih Sub-district at 56.40%. The main obstacles include inaccurate tax object data, limited human resources, and insufficient socialization. In response, Bapenda has innovated through the establishment of a Public Service Mall (MPP), strengthening of Regional Technical Implementation Units (UPTD), door-to-door Comb Operations (Opsir), and providing tax payment discounts. It is recommended to update and synchronize tax object data, optimize integrated information technology, improve human resource competency, and intensify tax socialization and literacy to the community.